(untitled) (Fiep Bulletin - online, 2011)
The nutritional assessment and the study of body composition are important to trace the nutritional profile of the athlete. The anthropometric and nutritional assessment of the soccer player should consider the fact that according to the positions taken in the field, the athletes will have a specific energy demand and a certain anthropometric standard. This research was classified as applied, quantitative with a deductive method. The research objective was to perform the anthropometric assessment and establish the feed profile of junior soccer players. The anthropometric assessment of 25 players with a mean age of 18.38 ± 1.39 years and mean height of 1.80 ± 0.064 m was performed. The goalkeepers and defenders presented more lean mass and higher percentage of fat mass. The wingers showed the lowest values for the analyzed data. When evaluating the feed rates of the players, it was observed that 72% (18 athletes) consume adequate amounts of carbohydrates, 48% (12 athletes) consumed the protein requirements and 28% (7 players) ingested quantities below the recommended for lipids, while the remainder exceeded these values. It was concluded that athletes who do not have the nutritional follow up usually have their body composition and eating habits outside the normal standard for the group in question.